HAX1 enhances the survival and metastasis of non‐small cell lung cancer through the AKT/mTOR and MDM2/p53 signaling pathway. Issue 11 (14th September 2020) - Liang, Zhigang; Zhong, Yuan; Meng, Lifei; Chen, Yi; Liu, Yahui; Wu, Aihua; Li, Xinjian; Wang, Mingsong
Abstract : Background: HS‐1‐associated protein‐1 (HAX1) has been reported to be overexpressed in non‐small cell lung cancer (NSCLC) tissues. However, the underlying mechanism of HAX1 in NSCLC has not previously been demonstrated. The present study investigated the role and underlying mechanism of HAX1 in NSCLC. Methods: The HAX1 expression were confirmed in NSCLC tissues through TCGA database and qRT‐PCR. Moreover, we performed qRT‐PCR, Western blotting, Transwell assays, TUNEL assays and so on to evaluate the role of HAX1 in A549 and H1299 cell lines. Results: mRNA expression of HAX1 was overexpressed in NSCLC tissues compared to adjacent normal tissues according to The Cancer Genome Atlas (TCGA) database. QRT‐PCR assays showed that HAX1 mRNA expression was upregulated in NSCLC tissues. The high HAX1 mRNA levels were found to be positively associated with tumor size, TNM stage and lymphatic metastasis. Silencing of HAX1 promoted apoptosis and reduced invasion of A549 and H1299 cells by inhibiting the AKT/mTOR and MDM2/P53 signal pathway. AKT agonist SC79 could inhibit apoptosis and promote proliferation, migration and invasion of A549 and H1299 cells transfected with si‐HAX1. Conclusions: The present study provided a better understanding of HAX1 mechanism in NSCLC and potential therapeutic target for NSCLC. Abstract : HAX1 enhances the survival, invasion and epithelial–mesenchymal transition of NSCLC cells through the AKT/mTOR signaling pathway. HAX1 play an important role in NSCLC and should be taken into consideration.